Effect of Relaxin on the Biological Activities of Cryopreserved Holstein Bull Semen after Different Periods of Incubation - Hussein, Rania Dhyaa; Banana, Husam Jasim Hussein; Mahammad, Omar Adel (Iraqi Journal of Science, 2026)
This study evaluated the effects of two relaxin concentrations (60ng/ml and 90ng/ml) combined with Tris (TC: control, T1: 60ng/ml, T2:90ng/ml) and soybean lecithin extender (SC: control, S1: 60ng/ml, S2:90ng/ml) on post-thaw sperm quality in Holstein bulls. Sperm parameters, including motility, viability, abnormalities, plasma membrane integrity, and acrosome integrity, were assessed over cryopreservation periods of 48 hours, one month, and two months, with post-thaw incubation for one and two hours. All treatments experienced a decline in motility and viability over time, but T1(60ng/ml in Tris) maintained significantly the highest motility compared to the control (TC) group (p≤0.05). Soybean lecithin extenders generally showed lower motility and viability, with S2(90ng/ml) performing the worst. One hour of incubation preserved sperm quality more effectively than two hours. Relaxin treatments improved the plasma membrane integrity, especially with soybean lecithin, and enhanced acrosome integrity, particularly in T2 and S2. However, higher relaxin concentration was associated with reduced motility and viability. Overall, T1 showed the best results, emphasizing the critical role of relaxin concentration optimization for improving post-thaw sperm quality and incubation time to enhance post-thaw sperm preservation.